Genotoxic, mutagenic, and cytotoxic analysis in bats in mining area - Benvindo-Souza, Marcelino; Sotero, Daiany Folador; dos Santos, Cirley Gomes Araújo [UNESP]; de Assis, Rhayane Alves [UNESP]; Borges, Rinneu Elias; de Souza Santos, Lia Raquel; de Melo e Silva, Daniela (Springer Nature, 2023)
Pollution generated by the mining industry can cause harm to wildlife. This study aimed to evaluate the cytotoxicity, genotoxicity and mutagenicity in bats environmentally exposed to open pit mining. Thus, 62 bats of the following species, Carollia perspicillata, Glossophaga soricina, Phyllostomus hastatus, and Desmodus rotundus exposed to mining activities (ferronickel) were used in the analysis. The animals were obtained in samplings in July and November of 2021, totaling 8 days of sampling in the field. The results indicated that species differ in the frequency of genotoxic damage between sampling points within the mining landscape. Cytotoxicity was observed by scoring of karyorrhexis, pyknosis and karyolysis. The most captured species, C. perspicillata, showed differences in DNA damage between exposed and unexposed populations, but no differences were observed between males (n = 14) and females (n = 20). G. soricina was also a sensitive species for indicating a high frequency of DNA damages compared to the omnivore P. hastatus. Elements such as Mn, Cr, Pb, and Zn observed in water samples were at high levels in the mining area. We conclude that bats in mining areas are susceptible to increased DNA damage as already identified for other species.
Keywords: Chiroptera; Comet assay; DNA damage; Micronucleus test